2011
DOI: 10.1111/j.1472-765x.2011.03023.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of phages infecting Bacillus cereus

Abstract: Aim:  To isolate and characterize bacteriophages (phages) that infect the foodborne pathogen Bacillus cereus. Methods and Results:  Two phages were isolated from soil based on their ability to form plaques on four indicator hosts including Bacillus thuringiensis subsp. israelensis, and three isolates of B. cereus. The purified phages were characterized by morphology, host range, single‐step growth curves and restriction enzyme digestion profiles. The phages appeared to be of the Myoviridae family based on thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 27 publications
4
31
0
1
Order By: Relevance
“…Results indicated that, phage active against Bt may be present in soil or integrated with host genome (lysogeny) or as independent linear replica within the cell. These results are in accordance with finding of [19,26,27,41,43,48]. Electron microscopic studies of the isolated phages (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results indicated that, phage active against Bt may be present in soil or integrated with host genome (lysogeny) or as independent linear replica within the cell. These results are in accordance with finding of [19,26,27,41,43,48]. Electron microscopic studies of the isolated phages (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Morphologically, these four phage virtually did not differ from 8 phages described by Azizbekian et al [11] and phage TB10 described by Ackermann et al [4]. The tail and capsid measured here are totally different from Bacillus cereus phages measured by The morphology of the plaque depends upon the phage, the host, and the growth conditions a At least ten measurements taken directly from negatives Bacillus thuringiensis and their phages 111 [26] Meanwhile, Phage YHS was appeared with very short tail and isometric polyhedral capsid. This phage belonged to the group C1 morph.…”
Section: Discussionmentioning
confidence: 49%
“…Cross-infectivity studies of Basilisk, JL, and Shanette were warranted because others have observed cross-infectivity of bacteriophages that infect the Bacillus genus (49)(50)(51) …”
Section: Resultsmentioning
confidence: 99%
“…For example, two phages, FWLBc1 and FWLBc2, which were isolated from soil, reduced the pathogen in mashed potato (by >6 log 10  cfu/mL during 24 h). Because of the phages' narrow lytic activity, it has been suggested to use them as a component of phage cocktails [114]. This high specificity may constitute a disadvantage in using phages against foodborne pathogens, due to the complex composition of bacteria that contaminate food.…”
Section: Bacteriophages In Foodborne Pathogen Disinfectionmentioning
confidence: 99%